2019
DOI: 10.1002/fsn3.1149
|View full text |Cite
|
Sign up to set email alerts
|

Using adaptive neuro‐fuzzy inference system and multiple linear regression to estimate orange taste

Abstract: In this research, some characteristic qualities of orange fruits such as vitamin C and acid content; weight; fruit and skin diameter; and red (R), green (G), and blue (B) values of the RGB color model for 70 samples were used to predict the taste of orange grown in Darab, southeast of Fars Province, Iran, by multiple linear regression (MLR) and adaptive neuro‐fuzzy inference system (ANFIS). To use MLR, firstly the most important input data were selected, and then, the best model to predict the taste of orange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Despite being viewed as ineffectual, MLR models are frequently employed in the modelling process and successfully validated. A study employing the MLR model to predict the flavor of orange using 70 samples is an example of this, and the results revealed that the prediction performance of the MLR model had a strong significant relationship between orange taste and vitamin C, red color, and blue color as reported by Mokarram et al [87]. Furthermore, eight aroma properties of Dianhong tea were predicted using MLR produced R 2 > 0.95 [46].…”
Section: Correlation Analysismentioning
confidence: 67%
“…Despite being viewed as ineffectual, MLR models are frequently employed in the modelling process and successfully validated. A study employing the MLR model to predict the flavor of orange using 70 samples is an example of this, and the results revealed that the prediction performance of the MLR model had a strong significant relationship between orange taste and vitamin C, red color, and blue color as reported by Mokarram et al [87]. Furthermore, eight aroma properties of Dianhong tea were predicted using MLR produced R 2 > 0.95 [46].…”
Section: Correlation Analysismentioning
confidence: 67%
“…In addition, Abbaspour-Gilandeh et al [113] designed a system combining artificial neural networks and ANFIS for predicting the kinetic energy and energy of quince under a hot air dryer, Kaveh [114] designed an ANFIS model for predicting the moisture diffusivity and specific energy consumption of drying potatoes, garlic, and melons under convection hot air dryers, Arabameri et al [112] utilized an adaptive neuro-fuzzy inference system (ANFIS) to assess and forecast the oxidative stability of virgin olive oil. Mokarram et al [115] employed an adaptive neuro-fuzzy inference system and multivariate linear regression to estimate the flavor of oranges. Table 2 lists the published ANFIS technology applications in the food industry.…”
Section: R Peer Review 14 Of 30mentioning
confidence: 99%
“…Tanhaei et al [18] described ANFILS as the model best in data prediction with very low error value. It is commonly used in production and other segment of industries [58][59][60][61][62]; agricultural processes [63] and separation processes for water treatment and purification [18,19,[64][65][66][67]. The dearth of insightful information on the response surface methodology (RSM), RSM-genetic algorithm (GA) and adaptive neuro-fuzzy inference logic system (ANFILS) modeling and optimization of the process variables involved in the adsorption of naphthalene adsorption on chitosan-CTAB-bentonite matrix necessitated this study, which, to the best of our knowledge, has not been reported in the literature.…”
Section: Cadmium Ionsmentioning
confidence: 99%